Penelitian Etnografi Komunikasi: Tipe dan Metode - Zakiah, Kiki (FIkom Unisba, 2008)
According to Hofstede, there are many approach to define culture: (1) culture as symbols; (2) culture as expressed by heroes; (3) culture as rituals; and (4) culture as a set of values. There are also many ways to investigate culture from communication perspective—ethnography of communication is one of them. Based on Lindlof and Taylor definition about ethnography of communication, this article outlined many issues from the definition of ethnography to methods, perspective and analysis unit. Ethnography of communication is a unique method of communication research that could be applied in many communication activities.